Barriers to the Implementation of the Merdeka Curriculum in Elementary Schools: A Systematic Literature Review - Adi, Nur Romdlon Maslahul; Fina Wardani (Journal of Practice Learning and Educational Development, 2025)
The Merdeka Curriculum has been gradually implemented across all levels of education in Indonesia since 2022 as a response to the need for more flexible, collaborative, and student-centered learning. However, its implementation at the elementary school level faces various challenges, both in terms of resource readiness and stakeholder acceptance. These obstacles, if not identified and addressed, have the potential to hinder the core objectives of the Merdeka Curriculum in improving education quality. Yet, few studies have synthesized these challenges comprehensively across recent empirical work, particularly at the elementary level, highlighting a research gap and the need for a consolidated overview that may contribute to curriculum implementation theory in elementary education. This study aims to identify and classify the barriers to the implementation of the Merdeka Curriculum in elementary schools through a Systematic Literature Review (SLR). Literature searches were conducted using Publish or Perish 7 and VOSviewer, with the keyword “Kurikulum Merdeka Sekolah Dasar” applied to Google Scholar–indexed articles published between 2022 and 2024. From 500 articles retrieved, 29 met the eligibility criteria for analysis. The findings reveal that the implementation constraints fall into three main categories: (1) facilities, including limited infrastructure, lack of technological devices, and insufficient funding for teaching aids; (2) teachers, particularly inadequate training and mentoring for transforming teaching practices; and (3) students, parents, and the environment, such as parental resistance to curriculum changes. The results enrich perspectives on curriculum implementation and teacher change by showing how structural limitations and incomplete professional learning restrict the realization of student-centered reform at the classroom level.